COMPARATIVE PERFORMANCE EVALUATION OF STEEL STRUCTURES USING KING CROSS, TUBE, AND WIDE FLANGE COLUMNS UNDER SEISMIC RESPONSE - Taofik Nurmeiyanto; Budiman Budiman (International Journal of Civil Engineering and Infrastructure, 2026)
Steel building structures must be designed to safely and efficiently resist gravity and lateral loads. One of the key factors influencing structural performance is the shape and type of column section used, as differences in geometric characteristics affect stiffness, strength capacity, and structural response to lateral loads, particularly seismic forces. This study aims to analyze the effect of using King Cross, Tube, and Wide Flange sections as columns in steel building structures on overall building performance under gravity and lateral loads. Structural modeling was carried out using ETABS software by developing three building models with identical configurations, dimensions, and loading conditions, differing only in the type of column section applied. All models were designed using a Special Moment Resisting Frame (SMRF) system. The results indicate that variations in column section types significantly influence structural performance, where sections with higher stiffness produce smaller inter-story drift and better lateral load response. Furthermore, differences in column sections affect the fundamental period of vibration, internal forces, and strength ratios of structural elements, which in turn impact the efficiency and safety level of steel building structures. These findings are expected to provide useful guidance for structural engineers in selecting the most suitable column section for a given design requirement.Keywords: steel column, King Cross, Tube, Wide Flange, ETABS, inter-story drift, SMRF